Ventilatory responses to constant load exercise following the inhalation of a short-acting ß2-agonist in a laboratory-controlled diesel exhaust exposure study in individuals with exercise-induced bronchoconstriction. (January 2021) - Koch, Sarah; Welch, Joseph F.; Tran, Raymond; Ramsook, Andrew H.; Hung, Andy; Carlsten, Christopher; Guenette, Jordan A.; Koehle, Michael S.
Highlights: Exercise while breathing diesel exhaust led to bronchodilation in adults with asthma. Lung function was maintained 60 min following exercise in diesel exhaust after β2 -agonist use. β2 -agonists reduced the mechanical work of breathing even with diesel exhaust. Perceived breathlessness was unaffected by diesel exhaust during exercise. Abstract: Objective: Individuals with exercise-induced bronchoconstriction (EIB) use ß2 -agonists to reduce respiratory symptoms during acute exercise. The resulting bronchodilation could increase the dose of inhaled pollutants and impair respiratory function when exercise is performed in air pollution. We aimed to assess respiratory responses in individuals with EIB when completing a cycling bout while being exposed to diesel exhaust (DE) or filtered air (FA) with and without the inhalation of salbutamol (SAL), a short-acting ß2 -agonist. Methods: In a double-blind, repeated-measures design, 19 participants with EIB (22-33 years of age) completed four visits: FA-placebo (FA-PLA), FA-SAL, DE-PLA, DE-SAL. After the inhalation of either 400 µg of SAL or PLA, participants sat in the exposure chamber for 60 min, breathing either FA or DE (PM2.5 = 300 μg/m 3 ). Participants then cycled for 30 min at 50 % of peak work rate while breathing FA or DE. Respiratory responses were assessed via spirometry, work of breathing (WOB), fractional use of ventilatory capacity ( V ̇ E / V ̇ E, CAP ), area under the maximal expiratory flow-volume curve (MEFVAUC ), and dyspnea during and following cycling. Results: Bronchodilation in response to SAL and acute cycling was observed, independent of FA/DE exposure. Specifically, FEV1 was increased by 7.7 % (confidence interval (CI): 7.2–8.2 %; p < 0.01) in response to SAL, and MEFVAUC was increased after cycling by 1.1 % (0.9–1.3 %; p = 0.03). Despite a significant decrease in total WOB by 6.2 J/min (4.7–7.5 J/min; p = 0.049) and a reduction in V ̇ E / V ̇ E, CAP by 5.8 % (5–6 %, p < 0.01) in the SAL exposures, no changes were observed in dyspnea. The DE exposure significantly increased V ̇ E / V ̇ E, CAP by 2.4 % (0.9–3.9 %; p < 0.01), but this did not affect dyspnea. Discussion: Our findings suggest that the use of SAL prior to moderate-intensity exercise when breathing high levels of DE, does not reduce respiratory function or exercise ventilatory responses for up to 60 min following exercise.